PENATAAN ORGANISASI: STUDI PADA DINAS PENGAIRAN DAN PEKERJAAN UMUM KABUPATEN LAMPUNG TIMUR (Administratio, 2018)
ABSTRACT. Organizational structuring provides many opportunities for the organization being studied and the method to be used. Organizational structuring is tailored to the environmental needs in which the organization lives. This study aims to describe the organization arrangement of the Public Works Irrigation Office in East Lampung Regency. The study was conducted with a descriptive qualitative approach, with data collection techniques through in-depth interviews, observation and documentation studies. The results of the study concluded that the establishment of the Dinas Pengairan and Public Works was in accordance with the needs and environmental conditions of the organization. However, the existing organizational structure needs to be adjusted to the needs and environment.